Nosocomial outbreak of Pseudomonas aeruginosa associated with a drinking water fountain. Issue 3 (November 2015) - Costa, D.; Bousseau, A.; Thevenot, S.; Dufour, X.; Laland, C.; Burucoa, C.; Castel, O.
Summary Over a four-month period, ten patients were suspected of having acquired nosocomial infection to P. aeruginosa in the ear, nose, and throat department. Environmental and clinical isolates were compared. Only water from a drinking water fountain was contaminated by P. aeruginosa. This isolate and those of three patients had indistinguishable random amplified polymorphic DNA profiles. These patients had serious oncology diseases. The drinking water fountain was used for their alimentation by percutaneous endoscopic gastrostomy and was the origin of the outbreak. Another type of drinking fountain with a terminal ultraviolet treatment was installed, following which no new infections linked to drinking water were identified.